UNCHARTED WATER: INDONESIA’S COPYRIGHT CHALLENGES IN THE DIGITAL AGE - Wa Ode, Zuliarti; Faisal, Fitriah (International Journal of Law in Changing World, 2025)
Digital technology has complicated copyright protection, particularly in Indonesia, where weak laws, poor enforcement, and low awareness fuel piracy. Modernizing regulations, improving enforcement, and promoting education about intellectual property rights are essential to fostering innovation, safeguarding creators, and supporting the creative economy in the digital era. This study evaluates Indonesia's copyright framework in the digital era, focusing on its legal adaptability, enforcement effectiveness, public awareness, economic impacts, and potential insights from global best practices to enhance the creative economy and tackle digital piracy challenges. This study employs comparative hermeneutics, including legal analysis of Indonesia's copyright laws, international benchmarks, and case studies of successful anti-piracy efforts to study enforcement mechanisms and economic impacts to offer actionable insights for effectively adapting Indonesia's copyright framework. The authors conclude that Indonesia must strengthen its legal framework; only by aligning with global standards like TRIPS can Indonesia safeguard creators’ rights, enhance enforcement, and ensure competitiveness in the digital economy. _____ AGUAS DESCONOCIDAS: LOS RETOS DE LOS DERECHOS DE AUTOR EN INDONESIA EN LA ERA DIGITAL La tecnología digital ha complicado la protección de los derechos de autor, especialmente en Indonesia, donde la debilidad de las leyes, la aplicación deficiente y la escasa concienciación fomentan la piratería. Modernizar las regulaciones, mejorar la aplicación y promover la educación sobre los derechos de propiedad intelectual son esenciales para fomentar la innovación, proteger a los creadores y apoyar la economía creativa en la era digital. Este estudio evalúa el marco de derechos de autor de Indonesia en la era digital, centrándose en su adaptabilidad legal, la eficacia de la aplicación, la concienciación pública, el impacto económico y las posibles perspectivas de las mejores prácticas globales para impulsar la economía creativa y abordar los retos de la piratería digital. Este estudio emplea hermenéutica comparativa, incluyendo un análisis legal de las leyes de derechos de autor de Indonesia, referentes internacionales y estudios de caso de iniciativas exitosas contra la piratería para estudiar los mecanismos de aplicación y el impacto económico, con el fin de ofrecer perspectivas prácticas para adaptar eficazmente el marco de derechos de autor de Indonesia. Los autores concluyen que Indonesia debe fortalecer su marco legal. Solo alineándose con estándares globales como el Acuerdo sobre los ADPIC, Indonesia podrá salvaguardar los derechos de los creadores, mejorar su aplicación y garantizar la competitividad en la economía digital. _____ 未知领域：数字时代印度尼西亚的版权挑战 数字技术使版权保护变得复杂，尤其是在印度尼西亚。该国法律薄弱、执法不力、意识低下，盗版现象猖獗。在数字时代，更新法规、加强执法和促进知识产权教育对于促进创新、保护创作者和支持创意经济至关重要。本研究评估了数字时代印度尼西亚的版权框架，重点关注其法律适应性、执法有效性、公众意识、经济影响以及借鉴全球最佳实践的潜在经验，以促进创意经济的发展并应对数字盗版挑战。本研究采用比较诠释学，包括对印度尼西亚版权法的法律分析、国际基准以及成功的反盗版案例，以研究执法机制和经济影响，从而为有效调整印度尼西亚的版权框架提供可行的建议。作者得出结论，印度尼西亚必须加强其法律框架；只有与《与贸易有关的知识产权协议》(TRIPS) 等全球标准接轨，印度尼西亚才能保障创作者的权利，加强执法，并确保在数字经济中的竞争力。